Design the SLA of SIAKAD Based on CMMI-SVC and ITILV3 Framework - Putri, Rachmah Agus; Ginardi, Raden Vinantius Hari (IPTEK Journal of Proceedings Series, 2019)
PTIPD is an IT support at UIN Malang, responsible for information technology. Have the vision to apply and develop information technology to realize a university as Cyber Campus and Cyber Community and mission which is to provide services to the academic community in the utilization of Information Technology. One of the information system services that play an important role is SIAKAD. So far the services of SIAKAD have not fully met the criteria from vision and mission made by PTIPD. Technical related problems often happen repeatedly and the job description is not organized. The problems above more or less shows that the quality and performance from SIAKAD service has not met the standard to support the vision and mission of PTIPD. The researcher used work method which is CMMI-SVC related to capability measurement, related to technical problem and Service Level Agreement (SLA) design based on ITIL V3 framework and FMEA method in weighing the value of SLA elements. The first thing to do is mapping the criteria and CMMI-SVC’s processes area, and then measured the capability level of the selected process area, after that is design of the SLA used ITIL V3 best practices and SLA's weight calculations used FMEA method. The result of the capability level shows level 0, which is the basic thing that must be met to reach level 1 is the existence of SLA. This thesis produced a design of Service Level Agreement document